Effect of Boundary Layer Evolution on Nitrogen Dioxide (NO2) and Formaldehyde (HCHO) Concentrations at a High-altitude Observatory in Western India - Mriganka Sekhar Biswas; G. Pandithurai; M. Y. Aslam; Rohit D. Patil; V. Anilkumar; Shrikant D. Dudhambe; Christophe Lerot; Isebelle De Smedt; Michel Van Roozendael; Anoop S. Mahajan (Aerosol and Air Quality Research)
Abstract Nitrogen dioxide (NO2) and formaldehyde (HCHO) are some of the most important trace gases in the atmosphere, acting as precursors for ozone formation and as pollutants at high concentrations. Although several observations of these species have been reported in the boundary layer, observations at high altitude sites are limited, especially in India. This study reports observations of NO2 and HCHO using the Multi AXis Differential Optical Absorption Spectroscopy (MAX-DOAS) technique at the High Altitude Cloud Physics Laboratory (HACPL), Mahabaleshwar in the rural Western Ghats region of India. Measurements were conducted during the pre-monsoon season between 25th April and 30th May 2018. The average NO2 mixing ratio was 0.19 ± 0.06 ppb (range: 0.03 ppb to 0.69 ppb). Typically, NO2 mixing ratios were found to increase from early in morning and reached a maximum in the afternoon, contrary to an expected diurnal profile dominated by photochemistry. The average HCHO mixing ratio was 1.6 ± 0.61 ppb (range: 0.16 ppb–4.5 ppb). HCHO mixing ratios also showed an increase from early in the morning and reach a maximum at ~3 pm in the afternoon after which a decrease was observed, peaking much later than expected from a photochemistry dominated profile. Using observations of the boundary layer height, back trajectories and the known photochemistry, we conclude that the observed diurnal variation in these two species is dominated by the mixing of emissions from the base of the mountain, resulting from the evolution of the boundary layer at the HACPL site.